2016
DOI: 10.1371/journal.pntd.0004671
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation in Autophagy-Related Genes Influences the Risk and Phenotype of Buruli Ulcer

Abstract: IntroductionBuruli ulcer (BU) is a severe necrotizing human skin disease caused by Mycobacterium ulcerans. Clinically, presentation is a sum of these diverse pathogenic hits subjected to critical immune-regulatory mechanisms. Among them, autophagy has been demonstrated as a cellular process of critical importance. Since microtubules and dynein are affected by mycolactone, the critical pathogenic exotoxin produced by M. ulcerans, cytoskeleton-related changes might potentially impair the autophagic process and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 15 publications
2
51
1
Order By: Relevance
“…This variant is not in LD with variants of the PRKN (a.k.a. PARK2)/PACRG cluster associated with leprosy, including that reported to be associated with Buruli ulcer by Capela et al 26 (r² = 0.007) ( Table 3). We then looked at the 35 SNPs reaching genome-wide significance in the GWAS performed on tuberculosis (eight independent variants in eight different chromosomal regions; Supplementary Data 3a) or leprosy (27 variants in 19 different chromosomal regions; Supplementary Data 3b).…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…This variant is not in LD with variants of the PRKN (a.k.a. PARK2)/PACRG cluster associated with leprosy, including that reported to be associated with Buruli ulcer by Capela et al 26 (r² = 0.007) ( Table 3). We then looked at the 35 SNPs reaching genome-wide significance in the GWAS performed on tuberculosis (eight independent variants in eight different chromosomal regions; Supplementary Data 3a) or leprosy (27 variants in 19 different chromosomal regions; Supplementary Data 3b).…”
Section: Resultsmentioning
confidence: 76%
“…No enrichment in P values either <0.01 or <0.001 was observed among these variants in our discovery sample, the best hit being rs58925751, located in the DEFB123 gene on chromosome 20 (P value = 4.13 × 10 −4 ). We then checked the evidence of association in our GWAS for the six variants displaying significant association with Buruli ulcer in the three candidate-gene association studies on Buruli ulcer performed to date [25][26][27] ( Table 3). Only one of these variants-rs2241880, a missense T300A variant located in the ATG16L1 gene-had a P value < 0.05 in our GWAS under the additive model with the same allelic effect (one-tailed P value = 0.015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in the previous study 27 , GG homozygotes were found to be protected against the ulcerative clinical form of Buruli ulcer, with an OR of 0.35 [0.13-0.90]. Strikingly, when focusing only on ulcerative cases of our discovery sample (255 ulcerative cases vs. 401 controls), the association was more significant (P value = 0.003), with an OR of 0.31 [0.14-0.68] (Table 4).…”
Section: Signals Overlapping With Previously Reported Associationsmentioning
confidence: 83%
“…These studies explored a total of seven genes selected on the basis of their involvement in MSMD, tuberculosis or leprosy. Significant association with Buruli ulcer was reported for common variants of six of these genes: SLC11A1 26 , PRKN, NOD2, and ATG16L1 27 and iNOS and IFNG 28 . We performed a two-stage case-control GWAS, to investigate…”
Section: Introductionmentioning
confidence: 99%